Dimitrie Cantemir, salvation of the sage and ruin of the sinful world - Feodorov, Ioana.
1 online resource.
Keywords: This is a thoroughly revised and expanded version of the first edition of the Arabic version of Dimitrie Cantemir’s The Divan or the Sage’s Dispute with the World (Ṣalāḥ al-ḥakīm wa-fasād al-ʿālam al-ḏamīm) (Iaşi, 1698), his first printed book, the earliest ethical treatise in Romanian literature and a testimony to his wide knowledge, reading, and proficiency in foreign languages. Completed in 1705 by Athanasius III Dabbās, Patriarch of the Antiochian Church (1684-1694, 1720-1724), the Arabic text is accompanied by the first translation into a modern language, English. Book III contains Cantemir’s version of the Latin work Stimuli virtutum, fraena peccatorum (Amsterdam, 1682) by the Unitarian Andzrej Wiszowaty (Andreas Wissovatius) of Raków (Poland), a chief representative of the Polish Brethren. Thus, in the space of twenty-three years Central-European Protestant ideas reached the Arab Christians of Ottoman Syria, by way of Greek and Arabic.